The postfeminist Queerization: From trans/gender Constructivism to the Elimination of Women (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
Queer theories emerge from postmodern nominalist constructivism underthe assumption that all things are discursive fictions, all ontology, asubstantialist and dualistic narrative, and there is nothing real outside ofsocio-linguistic constructions and deconstructions. In the case of sexualdifference, queer theories assimilate it to the hetero-normative signifiersof the old bio-political regime, and consequently abolished it by meansof an ideological operative that brings us today to a post-feminism withoutwomen, where the speaking subjects arbitrarily techno-producetheir bodies and sexualities. Assuming some philosophical assumptionsof new material realisms, the present article aims at making visible thehidden essentialism of postmodern constructivism, its barely disguisedfemino-phobia and the effective violence—symbolic and non-symbolic—that it implies for actual women, and feminist agenda.
Keywords: Linguisticism; performativity; undecidability; sexual difference; ontology.